Crime, Women and Information and Communications Technologies: Everyday Management of Insecurity in Santiago and Buenos Aires - Focas, Brenda Marisa (2025)
In recent decades, crime has become a public concern anda daily issue in Latin America. While much research has focused onorganized crime and crime prevention, less attention has been givento how crime affects the everyday lives of young women in cities. Thisstudy, based on interviews with women in Santiago, Chile, and BuenosAires, Argentina, reveals that their primary concerns are street harassment and sexual crimes, which mainly impact their mobility in the city.Women avoid relying on mass media for information, instead turning to their mothers and grandmothers as primary sources of knowledge and fear. Chilean women express higher levels of concern, significantly restricting their activities, particularly leisure, compared toArgentine women. Despite these differences, women in both countrieshave adopted technologies for self-protection, although their lives remain deeply affected by the fear of crime.